The Compliance of MSME Taxpayers with Tax Socialization as A Moderating Variable - Parulian Hutagaol; Se Tin Se Tin (Magister Akuntansi FB-UK.Maranatha, 2025)
This study attempts to analyze MSME taxpayer compliance with tax socialization as a moderating element. This study collects primary data from business owners of MSMEs in Indonesia via the use of questionnaires. Researchers selected to gather data from a sample of 103 people who filled out questionnaires distributed using a sampling approach called convenience sampling. The SPSS software package was utilized for data analysis, and in particular multiple linear regression model analysis. The findings suggest that taxpayer compliance is not significantly affected by tax incentive programs.. Tax socialization has no effect on the motivation to pay taxes . Knowledge of tax law is not moderated by tax socialization in a way that increases taxpayer compliance. Keywords: MSMEs; tax incentives; tax understanding; tax socialization; taxpayer compliance